Analysis of the Discipline Level of Grade XI Students at SMAS PGRI 2 Sampit in the 2025/2026 Academic Year - Dian Lestari; M. Qahfi; M. Hadianur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Student discipline is an important aspect in the success of the educational process; however, conditions in the field indicate that indisciplined behavior still exists among eleventh-grade students. This study aims to determine the level of discipline of eleventh-grade students at SMAS PGRI 2 Sampit in the 2025/2026 academic year. The study used a descriptive quantitative method with a Likert-scale questionnaire instrument distributed to 60 students through the technique of total sampling. The reliability test results showed a Cronbach Alpha value of 0.900 (very reliable), and of the 27 statement items, 26 were declared valid. Overall, the level of student discipline was at an average score of 3.45 (86.25%), which is included in the very high category. A total of 47 students (78.3%) were in the very high category, and 13 students (21.7%) were in the high category. The value. The lowest score was found in the time discipline indicator (P15 = 68%), while the highest score was found in the dress discipline and rule compliance indicators (P2 and P22 = 95%). No students were in the medium, low, or very low categories. These findings indicate that school discipline has been well internalized in the daily behavior of grade XI students.